Analysis of Behaviour of Over-Current Protective Relay in Low Voltage Power System - ., Louisa Endona Bundan (UNIVERSITI TEKNOLOGI PETRONAS, 2012)
Electrical protection is an important essence to ensure continuous and smooth power delivery in any power system. Protective relays are employed to minimize immediate effect of disturbances caused by failure in the power system. Over-current relays are one of the protective relays used to achieve these objectives. This report proposes the use of digital protective relay over electromechanical relay in the power system due to several reasons. The analysis of behaviour of digital directional over-current protective relay is modeled in 415V three phase power system of MLNG Sdn Bhd, Bintulu, Sarawak. The simulation carried out using MATLAB Simulink provides understanding of the operation of digital directional over-current protective relay in an industrial distribution power system, with startup inrush current and back up relay for safe operation is considered. The performance of the protective relay is compared with IEC 255-3 standard to validate the accuracy of the proposed model.